C–C coupling formation using nitron complexes. Issue 46 (13th November 2020) - Sevim, Mehmet; Kavukcu, Serdar Batıkan; Kınal, Armağan; Şahin, Onur; Türkmen, Hayati
Abstract : A series of Ru II (1 ), Rh III (2 ), Ir III (3, 4 ), Ir I (5 ) and Pd II (6–9 ) complexes of the 'instant carbene' nitron were prepared and characterized by 1 H- and 13 C-NMR, FT-IR and elemental analysis. They were used to form C–C coupling reactions. Abstract : A series of Ru II (1 ), Rh III (2 ), Ir III (3, 4 ), Ir I (5 ) and Pd II (6–9 ) complexes of the 'instant carbene' nitron were prepared and characterized by 1 H- and 13 C-NMR, FT-IR and elemental analysis. The molecular structures of complexes 1–4 and 6 were determined by X-ray diffraction studies. The catalytic activity of the complexes (1–9 ) was evaluated in alpha(α)-alkylation reactions of ketones with alcohol via the borrowing hydrogen strategy under mild conditions. These complexes were able to perform this catalytic transformation in a short time with low catalyst and base amounts under an air atmosphere. Also, the Pd II –nitron complexes (6–9 ) were applied in the Suzuki–Miyaura C–C coupling reaction and these complexes successfully initiated this reaction in a short time (30 minutes) using the H2 O/2-propanol (1.5 : 0.5) solvent system. The DFT calculations revealed that the Pd 0/II/0 pathway was more preferable for the mechanism.